Pertimbangan pemasangan implan gigi pada pasien lanjut usia - Grecila Susilo, Sonya; Ariesanti, Yessy (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: The elderly population is a group of people who are vulnerable have tooth loss so it is common to use of dental implant for replace it. Unfortunately, decreased function and changes in the condition of the tissues of the oral cavity and alveolar bones due to the aging process are often make installation of implant more complicated. Futhermore, in the elderly often found systemic diseases such as hypertension, diabetes mellitus, osteoporosis or cardiovascular diseases that affect the installation of implants. But if the quality and quantity of alveolar bone and soft tissue are adequate accompanied by a healthy elderly condition, it is possible that implant placement will be succesfull. Case Report: A 69-years-old male patient attended a clinic to replace his missing right lower teeth with permanent denture. After undergoing several examinations, it was decided to perform dental implant on tooth 46, diameter 3.8 mm and length 10.5 mm with a cemented-screw type PFM crown. The implant and PFM crown were successfully placed in tooth 46 and patients were comfortable with the implant without any complaints of pain. Conclusion: chronological age by itself is suggested as one of the risk factors for success, but it would not be a contraindication as long as the condition of the alveolar bone is adequate and systemic disease is well controlled.